?BACTERIAL FLORA IN MARINE SEDIMENTS OF THE EASTERN ANTARCTIC REGION WITH SPECIAL REFERENCE TO BERKILEN BAY (Biological Sciences - PJSIR, 2000)
In microbial analysis of marine muddy sediments from the Berkilen Bay area near Jinnah Antarctic Base of Pakistan, bacterial counts of aerobic heterotrophs were determined on Tryptic Soya Agar with additional NaC I (3.5%) incubated at 0°, 5°, 10°, 25° and 37° C for 2 days to 4 weeks. The mean bacterial count (Colony Forming Units, FUlg) of sediment was 1.2xl04 CFUg-1 at O°C;2.6x I03 CFUg-1 at SaC; I.1xl04 CFUS·I at 10°C; 2.7x I04 FUg-1at 25°C and 2.3x104 crUS-I at 37°C. Bacteria isolated were psychrotrophs rather than psycbrophilcs. Among the identified genera gram positive dominated the gram negative. Genera isolated in the order of predominance were Micrococcus, Moraxella, Staphylococcus, Bacillus, Pseudomonas and Flavobacterium. The percentage of unidentified bacteria was quite low.